EFFECT OF REMOVING OLEORESIN WITH VARIOUS CHEMICAL COMPOUNDS ON PHYSICAL AND MECHANICAL PROPERTIES OF KERUING WOOD (DIPTEROCARPUS SPP.) - Wiyono, Bambang; Nurwati, Nurwati (Indonesian Journal of Forestry Research, 2007)
Keruing  (Dipterocarpus spp.)  was  the  second  important  wood  export of   Indonesia. Unfortunately, this wood contains oleoresin that hinders its utilization. Currently, the method used to remove oleoresin from keruing is by soaking it into bollied sodium salt solution. Result of  this method is unsatisfactory because the residual heavy oleoresin might still appear on the wood surface. The study was conducted to determine suitable chemical compounds for removing oleoresin from keruing, and the effects on physical and mechanical properties of the wood. Four types of chemical compounds were tested, i.e. sodium chloride, oxalic acid, sulfuric acid, and nitric acid, each at the concentrations of  0.5 percent, 1.0 percent, and 1.5 percent. Wood samples were soaked in the boiling solution at different concentration level for seven hours. When the solution cooled down, the oleoresin exudated out of  the wood samples was separated. The oleoresin was weighed for recovery determination after air dried, and the wood samples were cut into smaller-sized specimens for the physical and mechanical testing (MOE, MOR, compression parallel to grain, hardness and density). Results showed that sulfuric acid was the best chemical compound for removing oleoresin, and the higher the concentration the greater the oleoresin recovery. The second best chemical compound was nitric acid at an optimum concentration of one percent. The soaking of keruing in sulfuric acid and oxalic acid solution resulted in paler wood color compare with the untreated wood sample. Nitric acid solutions caused the color of the wood surface to turn into yellow brownish. The physical and mechanical properties (MOE, MOR, compression parallel to grain, hardness and density) of the oleoresin-removed keruing were slightly lower than the untreated (control) samples.